Massive Transfusion Protocol Activation Does Not Result in Preferential Use of Older Red Blood Cells. (10th September 2014) - McDaniel, Lauren M.; Triulzi, Darrell J.; Cramer, James; Zuckerbraun, Brian S.; Sperry, Jason L.; Peitzman, Andrew B.; Raval, Jay S.; Neal, Matthew D.
Abstract : Widespread, anecdotal belief exists that patients receiving massive transfusion, particularly those for whom a massive transfusion protocol (MTP) is activated, are more likely to receive older red blood cells (RBCs). Retrospective review of blood bank records from calendar year 2011 identified 131 patients emergently issued ≥10 RBC units (emergency release (ER)) prior to obtaining a type and screen. This cohort was subclassified based on whether there was MTP activation. For comparison, 176 identified patients transfused with ≥10 RBC units in a routine fashion over 24 hours represented the nonemergency release (nER) cohort. Though the median age of ER RBCs was 5 days older than nER RBCs (ER 20, nER 15 days, P < 0.001 ), both fell within the third week of storage. Regardless of MTP activation, transfused ER RBCs had the same median age (MTP 20, no-MTP 20 days, P = 0.069 ). In the ER cohort, transition to type-specific blood components increased the median age of transfused RBC units from 17 to 36 days (P < 0.001 ). These data refute the anecdotal belief that MTP activation results in transfusion of older RBCs. However, upon transition to type-specific blood components, the age of RBCs enters a range in which it is hypothesized that there may be a significant effect of storage age on clinical outcomes.